Comprehensive characterization of complex glycosphingolipids in human pancreatic cancer tissues - Hořejší, Karel; Jin, Chunsheng; Vaňková, Zuzana; Jirásko, Robert; Strouhal, Ondřej; Melichar, Bohuslav; Teneberg, Susann; Holčapek, Michal (The Journal of biological chemistry, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most common causes of cancer-related deaths worldwide, accounting for 90% of primary pancreatic tumors with an average 5-year survival rate of less than 10%. PDAC exhibits aggressive biology, which, together with late detection, results in most PDAC patients presenting with unresectable, locally advanced, or metastatic disease. In-depth lipid profiling and screening of potential biomarkers currently appear to be a promising approach for early detection of PDAC or other cancers. Here, we isolated and characterized complex glycosphingolipids (GSL) from normal and tumor pancreatic tissues of patients with PDAC using a combination of TLC, chemical staining, carbohydrate-recognized ligand-binding assay, and LC/ESI-MS2. The major neutral GSL identified were GSL with the terminal blood groups A, B, H, Lea, Leb, Lex, Ley, P1, and PX2 determinants together with globo- (Gb3 and Gb4) and neolacto-series GSL (nLc4 and nLc6). We also revealed that the neutral GSL profiles and their relative amounts differ between normal and tumor tissues. Additionally, the normal and tumor pancreatic tissues differ in type 1/2 core chains. Sulfatides and GM3 gangliosides were the predominant acidic GSL along with the minor sialyl-nLc4/nLc6 and sialyl-Lea/Lex. The comprehensive analysis of GSL in human PDAC tissues extends the GSL coverage and provides an important platform for further studies of GSL alterations; therefore, it could contribute to the development of new biomarkers and therapeutic approaches.
Keywords: duktální karcinom slinivky břišní; monoclonal antibodies; Chromatography, Liquid; thin-layer chromatography; Lipidomics; gangliosidy; pancreatic cancer; liquid chromatography; glykosfingolipidy; tandemová hmotnostní spektrometrie; glycolipids; sphingolipids; Gangliosides; Carcinoma, Pancreatic Ductal; Glycosphingolipids; sulfoglykosfingolipidy; chromatografie kapalinová; chromatogram binding assay; Pancreatic Neoplasms; chromatografie na tenké vrstvě; Tandem mass spectrometry; lidé; lipids; Humans; nádory slinivky břišní; Tandem Mass Spectrometry; Chromatography, Thin Layer; Biomarkers, Tumor; nádorové biomarkery; Sulfoglycosphingolipids